Hesperozygis ringens (Benth.) Epling:caracterização dos órgãos vegetativos, análise histoquímicae atividade antifúngica do óleo essencial - Pinheiro, Carlos Garrido (2018)
Lamiaceae stands out for presenting species with potential to produce e ssential oils (EOs), and among them, Hesperozygis ringens (Benth.) Epling is classified. In addition to studies about the production of an essential oil (EO) and its possible bioactivities, the knowledge about the structural characterization of the species is fundamental, as well as the classes of constituents produced by the same. Theref ore, this study had the following objectives: to characterize structurally the vegetative organs of H. ringens ; to detect the classes of constituents produced; to optimize a method for extracting ergosterol from wood rot fungi; to evaluate the antifungal potential of the lea ves EO and its major constituent against the same fungi. Leaves, inflorescences, stems and roots were collected. The structural characterization occurred by microscopic analysis of included and fresh material. Leaves and petals were used for histochemical testes aiming to detect the available classes of constituents. Leaves and inflorescences EOs were extracted and chemically described. For the bioassays, the white rot fungi Ganoderma applanatum and Trametes versicolor , and the brown rot ones Gloeophyllum trabeum and Lentinus lepideus were selected. The fungi were cultivated in Petri plates containing culture medium covered by cellophane membrane. Mycelia o f each fungus w as collected to verify the wet weight and they w ere transferred to test tubes where 25% potassium hydroxide, distilled water and n heptane were added. The n heptane layers were collected and analyzed through spectrophotometry. After the EO e xtraction and chemical analysis, pulegone was isolated through column chromatography. EO and pulegone were diluted in ethanol and tested at concentrations of: 0.5, 0.75, 1.00, 1.25 and 1.50 µL mL 1 (EO) and 0.35, 0.71 and 1.05 µL mL 1 (pulegone). Negative and positive controls were also considered, evaluating: mycelial growth inhibition and mycelial growth rate (EO) and mycelial growth inhibition (pulegone). The influence of EO and pulegone on fungi ergosterol contents was analyzed. The characterization of vegetative organs evidenced the presence of non glandular and glandular trichomes of peltate type on leaf and stem. In root, phenolic idioblasts were found. Two types of crystals were detected in the plant: inulin in leaf and stem; hesperidin in root. By h istochemical tests , the following classes were detected: total, acid and neutral lipids; EOs; oil resins; proteins; phenolic compounds; flavonoids; and alkaloids. The EOs extracted from leaves and inflorescences presented pulegone as major constituent. T he calculated ergosterol contents showed that the optimized method for ergosterol extraction was successful. T he results of antifungal activity for EO and pulegone evidenced the fungistatic effect of the extractive against T. versicolor . Pulegone presented f ungistatic effect against G. applanatum and fungicide effect against T. versicolor . The EO and pulegone interfered in ergosterol contents of the white rot fungi. The results obtained evidence d the potential of H. ringens EO and pulegone for the development of botanical pesticides. T he described results can serve as stimulus for research aiming to verify o the r bioacitivities of the constituent classes produced by the plant.